(untitled) (Scientific journal of the Fergana State University, 2026)
This article emphasizes that the study of these unique traditions and ceremonies, national values and customs created in our country has always placed a number of important tasks before scientists. In the process of spiritual development of society, the synergy of national and universal values, their influence on the development of each other, their place and role in society, and the definition of specific tasks are of great practical epistemological importance. The theatrical art of society consists of a set of aesthetic values created and perceived in certain historical conditions, including the nature of the environment in which the nation lives, the attitude to the activities of the systems of the socio-political system, the aesthetic aspects of all material and spiritual values created, the pearls of literature and art in the life and activities of people.